2015
DOI: 10.1016/j.ultsonch.2014.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Sono-synthesis of biodiesel from soybean oil by KF/γ-Al2O3 as a nano-solid-base catalyst

Abstract: In this work, biodiesel has successfully prepared via ultrasonic method in a short time and low temperature by nano-solid-base catalyst (KF/γ-Al₂O₃). The catalyst was obtained by calcination of a mixture of KF and γ-Al₂O₃ m(KF)/m(γ-Al₂O₃) at 500 °C for 3 h. Nano-solid-base catalyst was characterized with scanning electron microscopy (SEM), transmission electron microscope (TEM), X-ray diffraction (XRD), Fourier transform infrared (FT-IR), thermal gravimetry (TG) and the Hammett indicator methods. The TEM image… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…Some researcher has tried to study the biodiesel production from edibleoils and non-edible oils by using heterogeneous catalyst with an ultrasonic system [19]. Shahraki et al [20] reported that transesterification catalysis of soybean oil by KF/g-Al 2 O 3 achieved with sono-synthesis. Pukale et al [21] studied transesterification of waste cooking oil in the presence of heterogeneous solid catalyst and the results of optimum conditions such as catalyst concentration of 3 wt.% of K 3 PO 4 and reaction time of 90 min gave a highest biodiesel yield up to 92.0%.…”
Section: Introductionmentioning
confidence: 99%
“…Some researcher has tried to study the biodiesel production from edibleoils and non-edible oils by using heterogeneous catalyst with an ultrasonic system [19]. Shahraki et al [20] reported that transesterification catalysis of soybean oil by KF/g-Al 2 O 3 achieved with sono-synthesis. Pukale et al [21] studied transesterification of waste cooking oil in the presence of heterogeneous solid catalyst and the results of optimum conditions such as catalyst concentration of 3 wt.% of K 3 PO 4 and reaction time of 90 min gave a highest biodiesel yield up to 92.0%.…”
Section: Introductionmentioning
confidence: 99%
“…The sharp band around 1385 cm −1 is assigned to the stretching vibration of Al–O–H groups due to hydrogen bonding with the Al 2 O 3 surface that was disappeared at the high calcination temperature . The peak was probably shifted to a higher wavenumber as a result of the formation of a new structure in the catalyst with the increase of the calcination temperature which can be assigned to the stretching vibration of Al–O–K groups in K 3 AlO 3 phases as well as the peaks at 1010 and 1470 cm −1 . Physically adsorbed water on the samples was observed at around 1636 and 3400 cm −1 .…”
Section: Resultsmentioning
confidence: 92%
“…Solid‐base catalysts usually contain a support such as alumina and zirconia , and one or more active phases such as a potassium component , . The supports are generally used to provide a more specific surface area and larger pores for active species, and active phases have the main role in converting the feedstock to biodiesel.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasonic assisted transesterification processes for biodiesel production can significantly shorten reaction time [10][11][12][13][14]. To be the best of our knowledge, the effect of ultrasound on the liquid-liquid heterogeneous reaction system could be divided into two aspects.…”
Section: Introductionmentioning
confidence: 99%